Detailed analysis of HTT repeat elements in human blood using targeted amplification‐free long‐read sequencing. Issue 9 (12th July 2018) - Höijer, Ida; Tsai, Yu‐Chih; Clark, Tyson A.; Kotturi, Paul; Dahl, Niklas; Stattin, Eva‐Lena; Bondeson, Marie‐Louise; Feuk, Lars; Gyllensten, Ulf; Ameur, Adam
Abstract: Amplification of DNA is required as a mandatory step during library preparation in most targeted sequencing protocols. This can be a critical limitation when targeting regions that are highly repetitive or with extreme guanine–cytosine (GC) content, including repeat expansions associated with human disease. Here, we used an amplification‐free protocol for targeted enrichment utilizing the CRISPR/Cas9 system (No‐Amp Targeted sequencing) in combination with single molecule, real‐time (SMRT) sequencing for studying repeat elements in the huntingtin ( HTT ) gene, where an expanded CAG repeat is causative for Huntington disease. We also developed a robust data analysis pipeline for repeat element analysis that is independent of alignment of reads to a reference genome. The method was applied to 11 diagnostic blood samples, and for all 22 alleles the resulting CAG repeat count agreed with previous results based on fragment analysis. The amplification‐free protocol also allowed for studying somatic variability of repeat elements in our samples, without the interference of PCR stutter. In summary, with No‐Amp Targeted sequencing in combination with our analysis pipeline, we could accurately study repeat elements that are difficult to investigate using PCR‐based methods. Abstract : We have applied an amplification‐free targeted sequencing protocol utilizing CRISPR/Cas9 (No‐Amp Targeted sequencing) to study repeat elements in the huntingtin ( HTT ) gene, where an expanded CAG repeat is causative for Huntington disease. Eleven clinical samples were investigated, and for all alleles the resulting CAG repeat count agreed with previous results based on fragment analysis. With No‐Amp Targeted sequencing, we can accurately sequence through repeat expansions that are difficult to investigate using PCR‐based methods while also studying somatic variability between cells.